Nonglacial origin for low-δ18O Neoproterozoic magmas in the South China Block: Evidence from new in-situ oxygen isotope analyses using SIMS - Wang, Xuan-Ce; Li, Zheng-Xiang; Li, X.; Li, Q.; Tang, G.; Zhang, Q.; Liu, Y. (Geological Society of America Inc, 2011)
Low-δ18O signatures in supracrustal rocks have been used as geochemical proxies for cold paleoclimates, e.g., glaciations. Unusual low-δ18O values found in Neoproterozoic igneous rocks in parts of the South China Block have thus been genetically linked to Neoproterozoic glaciation events. However, we report here new oxygen isotope compositions from Neoproterozoic magmatic zircons in central southern China using in-situ techniques that argue against such an interpretation.Our results show that (1) low-δ18O magmatic zircons started to appear in the South China Block from ca. 870 Ma, coinciding with the tectonic switching from Sibao orogenesis to postorogenic extension, which occurred more than 150 m.y. prior to the first glaciation event. The most abundant low-δ18O magmatic zircons have ages of 800–700 Ma. (2) The 830–700 Ma magmatic zircons are characterized by their bimodal nature of oxygen isotope compositions, i.e., mantle-like δ18O values (+4.4‰ to +5.8‰) and high-δ18O values (+9.3‰ to +10.8‰). (3) A sharp temporal change in maximum zircon δ18O values in the South China Block coincided with the onset of continental rifting and the possible arrival of a plume head. (4) No negative δ18O zircons have been identified in this study, contrary to previous studies. These features strongly argue against a glaciation origin for low to negative δ18O values in Neoproterozoic magmatic zircons from southern China. We propose that two stages of high-temperature water-magma interaction during plume-driven magmatism and continental rifting best explain the low-δ18O magmas. The most important implication of this study is that formation of such low-δ18O magmatic zircons was not necessarily related to glacial events and should not be used as a geochemical proxy for a cold paleoclimate.